Socio-demographic portrait of the applicant and the main motives for choosing the "Therapy and rehabilitation" speciality - S.V. Zakharov; O.B. Nekhanevych; O.O. Rusakova; O.V. Smolianova (Medičnì Perspektivi, 2024)
Rehabilitation and psychological support are becoming today's most urgent issues due to russian armed aggression. These needs will be long-lasting and increasingly significant. Since 2023, the Program of Medical Guarantees in Ukraine has been expanded regarding rehabilitation assistance. Additionally, volumes of the state-commissioned training of bachelors and masters in the speciality of "Therapy and rehabilitation" have been increased. It is well known that the quality of specialists trained by higher educational institutions largely depends on the motives behind the career choice. Knowledge about a student's socio-demographic status and his/her motivations to become a physical therapy and occupational therapy specialist can help understand future challenges and opportunities for the profession's development. This information can aid in elaborating strategies to promote the profession in the educational services market and to attract more applicants to choose the speciality 227 "Therapy and rehabilitation". The research aimed to compose the socio-demographic characteristics of the applicant for training in the speciality 227 "Therapy and rehabilitation", to investigate the motivational aspects of career choice and to establish the factors significant for motivation formation. To achieve this goal, a voluntary anonymous survey of 39 domestic applicants enrolled to complete the bachelor's degree program in speciality 227 "Therapy and rehabilitation" at Dnipro State Medical University was conducted. It was determined that the contingent of applicants is represented mainly by persons aged 16-18 (74%) with an active life position (90%). Additionally, most are familiar with the specifics of medical professions (62%) and have had previous personal or professional contact with physical therapy and occupational therapy (78%). The future career decision was mostly independent (84%), conscious, and influenced by the balance of internal and external motivational factors. It was typically made one to two years before taking degree course (72%). The primary motives for choosing the speciality 227 "Therapy and rehabilitation" while understanding its demand in today's conditions by applicants (82%) were "interest in medical science" (95%), "the desire to help others" (95%), "the opportunity to obtain a prestigious profession" (90%), "possibility of guaranteed employment" (90%) and "material interest/financial independence" (87%). Future specialists are aware of the importance of controlled acquisition of knowledge and skills (90%), the need for daily independent work (80%), and the significance of gaining practical experience during training (95%). They aim to achieve professionalism (59%), enhance communication skills (31%), build endurance (31%), and cultivate persistence (28%) and empathy (28%). Most applicants entering the speciality 227 "Therapy and rehabilitation" are goal-oriented, highly motivated, and prepared for rigorous study, which is the key to developing into competent and competitive specialists.